Understanding Exercise Behavior and Drop-Out through Meta-Motivational Dominance, Exercise Identity and Motives - Joanne Hudson (Journal of Motivation, Emotion, and Personality: Reversal Theory Studies, 2018)
Despite literature exploring interventions and strategies to encourage exercise adoption and maintenance, the dropout rate of irregular exercisers, particularly within the first six months of adoption, continues to reduce the effectiveness of such interventions. Whilst a body of literature exists exploring the dropout profile of clinical patients, less is known about the psychological and theoretical differences that discriminate exercise behavior and that could be indicative of susceptibility to dropout in the general population. Our study examines whether the metamotivational constructs of reversal theory (Apter, 1989), exercise motives, and exercise identity can discriminate between males’ and females’ exercise behavior, defined in relation to length of exercise participation, consistency (frequency of previous dropout) and the main type of exercise engaged in. We created an online survey to which 973 participants responded. We used MANOVA to determine whether exercise length, consistency, or type resulted in significant differences in levels of outcome variables. Where we identified significant effects, we employed discriminant function analysis to determine whether and how the dependent variables were able to discriminate between groupings. Results indicated that differing profiles of exercise identity, metamotivational dominance, and motives for exercise could discriminate between females and males who had been exercising for different lengths of time, with different levels of exercise consistency and differing types of main exercise. Our findings indicate that specific groupings may highlight individuals who are vulnerable to dropout so that strategies can be tailored more effectively for these individuals and support more appropriate strategies to develop internalized motivation.